2014
DOI: 10.1002/btpr.1874
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput miniaturized bioreactors for cell culture process development: Reproducibility, scalability, and control

Abstract: Decreasing the timeframe for cell culture process development has been a key goal toward accelerating biopharmaceutical development. Advanced Microscale Bioreactors (ambr™) is an automated micro-bioreactor system with miniature single-use bioreactors with a 10-15 mL working volume controlled by an automated workstation. This system was compared to conventional bioreactor systems in terms of its performance for the production of a monoclonal antibody in a recombinant Chinese Hamster Ovary cell line. The miniatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 24 publications
0
81
0
Order By: Relevance
“…Concern over the lack of control of process parameters during screening led to significant interest in the use of microbioreactors to enable assessment of clones under controlled pH and DO conditions for better screening outcomes 60,61 . Simcell was among the first microbioreactor to be commercially available with culture volumes of less than a millilitre 62 .…”
Section: Strategies For High and Medium Throughput Clone Screeningmentioning
confidence: 99%
“…Concern over the lack of control of process parameters during screening led to significant interest in the use of microbioreactors to enable assessment of clones under controlled pH and DO conditions for better screening outcomes 60,61 . Simcell was among the first microbioreactor to be commercially available with culture volumes of less than a millilitre 62 .…”
Section: Strategies For High and Medium Throughput Clone Screeningmentioning
confidence: 99%
“…The demand for monoclonal antibody products has resulted in a significant amount of global manufacturing capacity devoted to their production as well as to significant improvements in methods and approaches to monoclonal antibody manufacturing process design and optimization. [8][9][10][11][12] The forty-seven monoclonal antibody products on the market in the US and Europe as of November 10, 2014 are listed in Table 1. In 2013, eighteen of these monoclonal antibody products (Humira, Remicade, Enbrel, Rituxan, Avastin, Herceptin, Lucentis, Erbitux, Synagis, Eylea, Soliris, Tysabri, Stelara, Xolair, Orencia, Simponi, Actemra, and Xgeva) achieved annual sales of over $1 billion, while six of these products (Humira, Remicade, Enbrel, Rituxan, Avastin, Herceptin) had sales of greater than $6 billion.…”
Section: Growth Of the Monoclonal Antibody Marketmentioning
confidence: 99%
“…Data presented in Chapter 5 and in other studies 34,169,170,[172][173][174]192,193 showed that the current mL-scale systems are promising tools to be integrated into process characterization and design space exploration during upstream process development. Current research is focusing on the further implementation of mL-scale systems into process development and replacing the traditional bench-scale bioreactors with mLscale systems (Figure 1).…”
Section: Introductionmentioning
confidence: 94%
“…It was shown that the physical environment between the ambr and conventional STRs differs in some aspects including the flow regime, gas superficial velocity, and volumetric power input. Several studies have been performed to compare the culture performance of the ambr system to STRs ranging from 2 L up to 1000 L for CHO cell fed-batch processes [169][170][171][172] . Overall, similar process performances were reported across all scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation